Kinetic and equilibrium studies of doxorubicin adsorption on MCM-41-type silica surface - N. V. Roik; L. A. Belyakova; M. O. Dziazko (Хімія, фізика та технологія поверхні, 2016)
Doxorubicin belongs to the most widely used anticancer chemotherapy drugs. Yet the long?term treatment with doxorubicin is associated with toxic side effects. Minimization of undesired damages of healthy cells without reducing therapeutic action of doxorubicin can be attained using drug carrier systems, particularly silica nanoparticles. The aim of this work was elucidation of the probable mechanism of interaction between doxorubicin and silica surface. The adsorption of antitumor drug on mesoporous silica nanoparticles of MCM-41-type was studied depending on the contact time, pH of phosphate buffer solution, and doxorubicin concentration by use of UV-Vis spectroscopy. Experimental kinetic curves of adsorption were compared with theoretical models of Lagergren and Ho-McKay for pseudo-first and pseudo-second order processes. High correlation coefficients indicate that the kinetics of drug adsorption on silica surface at pH 5.0 and 7.0 can be fitted by pseudo-second order kinetic model. Equilibrium adsorption of doxorubicin was analyzed by Langmuir, Freundlich, Redlich?Peterson, and Brunauer?Emmet?Teller isotherm models. BET model is the most appropriate for prediction of doxorubicin equilibrium adsorption on MCM-41 silica from solutions with pH 7.0, whereas drug adsorption at pH 5.0 can be described by Freundlich model. The results obtained for doxorubicin adsorption kinetics and equilibrium on MCM-41 surface can be useful for comparative analysis of chemically modified silicas effectiveness.